THE TECHNOLOGICAL DEVELOPMENT OF THE STUDY OF ISLAMIC EDUCATION - Ali Muhdi; Mudzakir; Nur Faiz Habibah; Ilham Fadhilah; Lily Hidayani (International Journal of Teaching and Learning, 2024)
The method used is library research, which means that the data obtained is based on the results of library studies, sources from books, journals and documents that support the study variables. The results of the research showed that: 1. when developing print media such as the above, there are six things to be taken into account, namely: a. consistency in formatting the writing; b. format is adapted to the material to be created; c. organization, meaning how the print media design is made always provides information on the reader's position; d. attraction, the purpose of attracting interest and motivating the readers; e. font size, adapted with the reporter's target; and f. empty space, or space cosmosng can be stored in:a. space around the judo, b. wide edge boundary, c. space between columns, e. beginning of paragraphs, and f. space between lines (to improve viewability and readability) and paragraph adjusted.( untuk meningkatkan tingkat keterbacaan). 2. The steps to be taken in developing the teaching media with the print technology approach are by: a. formulate the goals of the students of Islamic education clearly, can be achieved, and viewed as a problem; b. present a hypothesis; c. evaluate the outcome of the lesson as a test of the hypotheses; and d. revision if the aim of learning Islamic Education has not yet been reached as indicated by the learning results of the pupils.